Posterior Capsular Opacification after PMMA and Hydrophobic Acrylic Intraocular Lens Implantation - Anwar Ul-Haq Ahmad, Muhammad Moin, Kashif Raza (Pakistan Journal of Ophthalmology, 2009)
Purpose: To compare the incidence of posterior capsular opacification after implantation of Hydrophobic Acrylic and polymethylmethacrylate (PMMA) intraocular lenses (IOLs). Material & Methods: A retrospective chart review of all patients undergoing phacoemulsification with implantation of posterior chamber IOL by a single surgeon from February 2000 to April 2007 was done in this study. The operated eyes of the patients were divided into 2 groups. Group A eyes were implanted a PMMA IOL (LX10 BD, Alcon) while group B eyes were implanted a Hydrophobic Acrylic (Acrysof multi-piece, Alcon) IOL. A detailed analysis of the charts was done to identify all the patients in both groups who presented with decreased visual acuity due to posterior capsular opacification (PCO) more than 2 years after cataract surgery. The charts of these patients were further screened to identify those patients who had visually significant PCO (best corrected visual acuity of <6/9) requiring YAG posterior capsulotomy. Patients with any posterior capsule plaque or rupture per-op, IOL implantation in the sulcus and significant macular disease were excluded from the study. Results: A total of 358 eyes underwent phacoemulsification with IOL implantation. There were 166 eyes in group A in which 5.5 mm PMMA IOLs (LX10 BD, Alcon) were implanted and 192 in group B eyes in which Hydrophobic Acrylic IOLs (Acrysof, Alcon) were implanted. In group A, 39.(23.4%) eyes with PMMA IOL had decreased vision due to PCO out of which only 10 patients (6%) underwent YAG posterior capsulotomy for significant visual loss. In group B, 12 (6.2%) eyes with Hydrophobic Acrylic IOL had decreased vision due to PCO out of which only 3 patients (1.5%) underwent YAG posterior capsulotomy for significant visual loss. Conclusion: Hydrophobic Acrylic IOLs have a lower rate of posterior capsular opacification compared to PMMA IOLs.